FERMENTASI BUNGKIL BIJI JARAK (Jatropha curcas L) SEBAGAI BAHAN KONSENTRAT RANSUM DOMBA - , H. Fatmawati; , Ir. Hari Hartadi, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
n using Rhizopus oligosporus and promote better performance of the animals. curcas L) AS MIXE Fatmawati R Experiments are conducted to evaluate nutritional value of Jatropha kernel cake (JKC). In first experiment, the cake is fermented using Neurospora crassa, Aspergillus niger or Rhizopus oligosporus and afterward are evaluated their chemical compositions, fiber fractions and content of its phorbol ester, an anti quality in JKC. The results showed that fermentation increased CP and decreased fiber fractions. The phorbol ester content (mg/g) of the JKC is decreased from 6.53 to 0.37, 0.14 and 0.10 when fermented (JKCF) using Aspergillus niger, Neurospora crassa, and Rhizopus, respectively. It is concluded that the Rhizopus has been selected to be applied in the next experiment based on the results and the ease of the requirements for growing it during fermentation. The second experiment is conducted to measure in situ rumen degradation of the JKC. The fermentation using Rhizopus oligosporus increased DTOM (%) from 55.78 to 61.06 when compared to the JKC, and increased OMD (%) from 28.13 to 45.55 when measured using two stages in vitro digestion. A study is also conducted in this experiment, 15 rats are fed three diets of commercial feed (FC), 30% FC and 70% JKC, or 30% FC and 70% JKCF. Results indicated that all rats in JKC diet were died in eight days. The third experiment is conducted to measure intake and digestibility of diets containing JKCF in the concentrate of 15 sheep. The sheep are offered elephant grass as basal diet and supplemented with concentrate without (0%), 6% or 12% of JKFC. All three diets are met the requirements of the sheep. The results showed that supplementation of JKFC increased intake of DM, CP, and TDN, and also increased OMD. Average daily gains of the sheep are significantly increased with supplementation of JKCF, being: 63.53, 76.80 and 96.38 g/head/day for 0, 6, and 12% of JKCF supplementation, respectively. Supplementation of JKCF up to 12% did not alter normal physiological aspects of the animals. The conclusion is that anti quality in the JKC is decreased by fermentatio